ANALISIS HASIL PEMBELAJARAN PENDIDIKAN JASMANI OLAHRAGA DAN KESEHATAN (PJOK) PADA SISWA KELAS VIII SMP NEGERI 25 PEKANBARU - Nofrianto, Neldi; Juita, Ardiah; Vai, Aref (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: The aim to be achieved in this research is to determine the learningoutcomes of Physical Education, Sports and Health (PJOK) for class VIII students atSMP Negeri 25 Pekanbaru. The population in this study was all Class VIII students atSMP Negeri 25 Pekanbaru, totaling 247 students. This number is more than 100 people,so by determining a sample size of 15%, the sample size is 37 people using theproportional random sampling technique. The instrument in this research is aquestionnaire distributed to respondents consisting of 2 questionnaire tables, namelytables with internal and external factors. Based on the results of the research anddiscussion, it can be concluded that the learning outcomes of Physical Education,Sports and Health (PJOK) in Class VIII Students of SMP Negeri 25 Pekanbaru from theinternnal factor were in the very high category with an average score of 94.45% and theexternal factor was in the very high category. high with an average value of 91.93% andfrom these 2 factors with an average value of 93.19% with a very high category.Key Words: Learning Result, Physical Education, Student